Studies of the environmental and endocrine control of reproduction in the four striped field mouse, Rhabdomys pumilio - Jackson, Claire (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2003)
Previous studies of the control of reproduction in Rhabdomys pumilio have shown that day length alone does not inhibit spermatogenesis, that a reduction in food availability and ambient temperature results in an inhibition of gametogenesis, that females are more susceptible to inhibition than are males, and that mice that are able to maintain a body fat store in the face of an energetic challenge, are less likely to show reproductive inhibition than those that lose their fat store. In the present study, field and laboratory experiments were conducted to examine the effects of winter food supplementation on reproduction and population dynamics, and the effects of exogenous GnRH, leptin and mercaptoacetate (MA) on reproductive activity of Rhabdomys pumilio exposed to an energetic challenge. In the field food supplementation experiments in Thomas Baines Nature Reserve (2000, 2001), there was no winter inhibition of reproduction and provision of supplementary food had little effect. While at Mountain Zebra National Park (2002) winter was harsher, females became reproductively inactive, spermatogenesis continued and the provision of extra food resulted in higher rates of individual growth and larger reproductive organs. Treatment of mice that had been exposed to a prolonged energetic challenge, with exogenous GnRH (1µg/mouse/treatment) resulted in an increase in the masses of the testes and epididymides, and in the activity of the reproductive organs. Treatment with exogenous leptin (40µg/mouse/treatment), concurrently with an energetic challenge, countered the negative effects of the energetic challenge, and treated males had larger reproductive organs. MA (600µmol/kg body mass), given concurrently with an energetic challenge, did not inhibit fat metabolism, although the high-fat diet countered the effects of the energetic challenge. Results suggest that the first response of male Rhabdomys pumilio to an energetic challenge is a reduction in the size of the reproductive organs, without an inhibition of spermatogenesis. It is likely that this effect is mediated via white fat and leptin, and leptin's influence on the hypothalamic-pituitary-gonad axis. Results of the study support the suggestion that females are more sensitive to reproductive inhibition than males and that reproduction in Rhabdomys pumilio is truly opportunistic.
Keywords: Microtus; Microtus -- South Africa -- Reproduction; Mice -- Reproduction